Gestão da segurança da informação: criação de uma política de informação para uma instituição de ensino médio na cidade de Americana - CARVALHO, Luiz Claudio (004, 2020)
Este trabalho apresenta a construção de uma política de segurança da informação para uma instituição pública de ensino médio localizada na cidade de Americana – SP, com os principais elementos necessários para o seu desenvolvimento, visando à implantação de uma cultura de segurança, contextualizada nos interesses e possibilidades de gestão pública. Como parte principal do desenvolvimento, são apresentadas as melhores práticas para a proteção e controle da informação, com a utilização de COBIT (Commom Objectives for Information and Related Technology), ITIL (Information Technology Infastructure Library) e a Norma NBR ISO/IEC 27002, interligadas.

This work presents the construction of an information security policy for a public high school institution located in the city of Americana - SP, with the main elements necessary for its development, aiming at the implantation of a security culture, contextualized in the interests and possibilities of public management. As the main part of the development, the best practices for the protection and control of information are presented, with the use of COBIT (Commom Objectives for Information and Related Technology), ITIL (Information Technology Infastructure Library) and the NBR ISO / IEC 27002 Standard, interconnected.
Information security management: creation of an information policy for a high school institution in the city of Americana
Keywords: Gestão da segurança em sistemas computacionais; Governança; Sistemas de informação; Política de informática; Informação e Comunicação